Gender, Genre, and Succession: Reception of Statius’ Achilleid in Baroque Opera - Kajetan Škraban (Keria: Studia Latina et Graeca)
The paper examines the reception of the Achilleid, an epic fragment by the Flavian poet Statius, in the Baroque opera. The Achilleid weaves unique connections among the issues of gender, succession, and genre, and as such merits an important place in studying the operatic reception of antiquity. The elements mentioned above (gender, succession, genre, as well as transvestism etc.) have been significant in establishing the opera as an art form; indeed, in the light of their historical influence some of the operatic works inspired by Statius may be perceived as major, well-nigh constitutive building blocks of the operatic art.